Bearing Capacity Factor for Spudcans in Anisotropic Clay Based on AUS Failure Criterion - Keawsawasvong, Suraparb (Science & Technology Asia, 2022)
New plastic solutions of spudcan foundations in anisotropic clay are presented in this paper. It is well known that natural clays exhibit some degree of strength anisotropy due to their deposition and sedimentation processes. Despite the important aspect of anisotropic clay, there is no existing solution for the bearing capacity of spudcans in anisotropic clay in the literature. An efficient numerical technique, namely the finite element limit analysis, is employed to derive the bearing capacity solutions of such foundation, where the Anisotropic Undrained Shear (AUS) failure criterion is associated with the computations. This failure criterion consists of three unequal undrained shear strengths obtained from the triaxial compression test, triaxial extension test, and direct simple shear test. In this paper, new solutions of the bearing capacity of spudcans in anisotropic clay are first-time derived based on two major dimensionless parameters, which are the cone apex angle and the undrained shear strength ratio obtained from the triaxial compression test and triaxial extension test. In addition, the failure mechanisms of the spudcans are examined and discussed to portray the effects of two major dimensionless parameters. The proposed solutions in this paper can be used as design charts for general design purposes of several offshore structures.